Ischemic cardiomyopathy and thyroid alterations: from the energetics of calcium homeostasis to cardioprotection in rat cardiac models - Bayley, Matias (2019)
Thyroid diseases affect cardiac Ca2+ homeostasis and induce long-term pathologies such as hypertrophy and remodelation. The consequences of cardiac ischemia-reperfusion (I/R) are still worse in a hyper- or a hypothyroid patient. The aim of this project is to characterize the myocardial mechanisms of hyperthyroidism (HypT) and hypothyroidism (HypoT) in the postischemic dysfunction, especially the mitochondrial role in two models of stunning due to I/R. HypT rats were obtained by daily SC injection of 20 μg.kg-1 triyodothyronine, and HypoT rats by drinking 0.02% methymazol, both during 15 days. Results were compared with rats without treatment (euthyroid, EuT). Ventricles were perfused in a flow calorimeter (37ºC-3Hz). Intraventricular contractile pressure (P, mmHg), diastolic contracture (ΔLVEDP) and total heat rate (Ht, mW.g-1) were measured, and the total muscle economy (Eco=P/Ht) was calculated. Isolated hearts were exposed to one of two models of I/R: moderate (20 min I) or severe (30 min I) followed by 45 min R (mI/R or sI/R, respectively). HypT was cardioprotector in mI/R because it increased the post-ischemic contractile recovery (PICR) to 108±12% of preischemic P (vs 70±6% in EuT, p<0.05) and Eco to 9.7±1.7*mmHg.mW-1(vs 3.6±0.6 in EuT,*p<0.05), reducing ΔLVEDP. Preischemic perfusion of clonazepam (Clzp, inhibitor of mitochondrial Na+/Ca2+-exchanger, mNCX) and 5-hydroxidecanoate (5-HD, blocker of mitochondrial ATP dependent-K+ channels, mKATP) in HypT reduced the PICR to 13.0±3.8%* and 68±14%* respectively (*p<0.05 vs HypT) and Eco to 0.6±0.1* and 4±1*mmHg.mW-1 respectively (*p<0.05 vs HypT). Clzp and 5-HD did not change PICR in EuT. In contrast, Ru-360 (blocker of mitocondrial Ca2+ uniporter, UCam) strongly reduced PICR and Eco in HypT and EuT. In sI/R, HypT and EuT showed low PICR and Eco, it was reversed by Cys-A (inhibitor of mitochondrial permeability transition pore, mPTP). HypoT was cardioprotector in both, mI/R and sI/R. In mI/R, HypoT improved PICR to 92±5%* (vs 69±6% in EuT,*p<0.05) and reduced ΔLVEDP. Clzp reduced PICR and Eco (36.7±6.4% and 38.4±7.4%, respectively) and increased ΔLVEDP to 86±15mmHg in HypoT. In sI/R, HypoT also increased PICR up to 54.5±6.0 % (vs 11.6±4.7% in EuT) and Eco up to 2.9±0.4mmHg.mW-1 (vs 1.0±0.4mmHg.mW-1 in EuT) and reduced ΔLVEDP. Clzp and 5-HD respectively reduced PICR to 29.4±7.7%* and 9.4±3.2%* (*p<0.05 vs HypoT) and Eco (1.4±0.4* and 0.4±0.2*,*p<0.05 vs HypoT), increasing ΔLVEDP. L-NAME (NOS-inhibitor) improved PICR up to 84.8±6.7 %*(*p<0.05 vs HypoT) and Eco. Nitroprusiate (NO-donnor) did not induce changes. Wortmanine or chelerythrine (inhibitors of PI3K/Akt and PKC, respectively) reduced PICR (to 6.8±0.6%* and 7.7±2.7%*,*p<0.05 vs HypoT) and Eco, increasing ΔLVEDP in HypoT. However, perfusion with adrenaline reduced the HypoT cardioprotection, which was reversed by oral 20mg/kg/day carvedilol (β-blocker). Conclusions: a)The HypT was cardioprotector only in mI/R, and it was due to activation of mNCX and mKATP which reduced Ca2+ overload responsible of mPTP opening in hearts exposed to sI/R; b)The HypoT was cardioprotector in both models of I/R. In sI/R, cardioprotection was related to activation of PI3K/Akt and PKC pathways, and reduction of Ca2+ overload by activation of mNCX and mKATP; c)The NOS-activation and adrenaline perfusion avoided cardioprotection, but carvedilol prevents the adrenergic dysfunction.Perspectives: To evaluate the mechanisms in Ca2+ homeostasis of carvedilol and nebivolol cardioprotection in HypoT and HypT hearts, through measuring Ca2+ transitories and waves in isolated cardiomyocytes as well as energetic of isolated hearts.